Bioinformatic Analysis and Translational Validation of Psoriasis Candidate Genes for Precision Medicine - Li AH; Li WW; Yu XQ; Zhang DM; Liu YR; Li D (Dove Medical Press, 2022)
An-Hai Li,1 Wen-Wen Li,2 Xiao-Qian Yu,3 Dai-Ming Zhang,4 Yi-Ran Liu,5 Ding Li1 1Department of Dermatology, Qingdao Huangdao District Central Hospital, Qingdao, People's Republic of China; 2Department of Hematology, Qingdao Women and Children's Hospital, Qingdao, People's Republic of China; 3Department of Dermatology, Qingdao Haici Hospital (Qingdao Traditional Chinese Medicine Hospital), Qingdao, People's Republic of China; 4Department of Pharmacy, Affiliated Hospital of Qingdao University, Qingdao, People's Republic of China; 5College of Traditional Chinese Medicine, Weifang Medical College, Weifang, People's Republic of ChinaCorrespondence: Ding Li, Department of Dermatology, Qingdao Huangdao District Central Hospital, Qingdao, People's Republic of China, Email 907325791@qq.comBackground: Psoriasis is a recurrent, chronic, inflammation- and immune-mediated skin disease with multiple causative factors. However, the genetic markers associated with recurrence have not yet been fully elucidated. Accordingly, in this study, we aimed to identify markers associated with the recurrence of psoriasis.Methods: We analyzed differentially expressed genes to determine which targets were associated with the recurrence of psoriasis and used these data to construct a protein-protein interaction network using Cytoscape software. The results were then validated by analysis of core targets using Gene Expression Omnibus (GEO) datasets and clinical samples. Functional enrichment analysis was used to explore the potential mechanisms mediating the recurrence of psoriasis.Results: We screened out six core targets that played important roles in recurrence of psoriasis, and validation of GEO datasets and clinical samples showed that the expression levels of five core targets were higher in patients with psoriasis than in healthy individuals. Functional enrichment analysis revealed that the cell cycle and oocyte meiosis signaling pathways were involved in the recurrence of psoriasis.Conclusion: Our findings provided insights into the mechanisms mediating the onset and recurrence of psoriasis.Keywords: psoriasis, recurrence, cell cycle, gene expression profiling, pathogenic mechanism